Integrating Structural and Non-structural Flood Management Measures for Greater Effectiveness in Flood Loss Reduction in the Kelantan River Basin, Malaysia - Ngai, Weng Chan; Ghani, Aminuddin Ab; Samat, Narimah; Hasan, Nik Norma Nik; Mou, Leong Tan (Springer Nature, 2019)
The state of Kelantan in Malaysia is a flood-prone state exposed to seasonal Monsoon rains that bring seasonal floods resulting in significantly losses. Flood management in the state is modelled after the country’s predominant government-centric top-down approach focused on flood-control technologies via structural measures such as multi-purpose dams, levees, embankments, tidal gates, diversion channels and others. These structural measures do not engage the public who fail to understand the measures leading to lack of confidence, misunderstanding and mistrust. This results in ineffectiveness of the measures leading to greater flood losses. In contrast, local communities are familiar with non-structural measures which they have long used to adapt to floods. These measures are also relatively simple, cost-effective and easily implementable over a short period of time. Both measures, however, must engage the public/victims in all phases of the flood disaster cycle. Balancing both types of flood management measures is the key to more effective management. A combination of structural and non-structural measures is the way forward for Kelantan State as it ensures that government structural measures are effectively supported by public-engaged non-structural measures.